Preparation method and application of mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation

By introducing nanospherical barium sulfate inorganic particles and fluoropolymers into the polypropylene hollow fiber membrane, the problems of low gas separation efficiency and susceptibility to contamination of membrane pores during the wastewater deamination process are solved, and higher gas separation efficiency and better backwashing performance are achieved, reducing the preparation cost.

CN116550165BActive Publication Date: 2025-05-02SHANGHAI UNIV OF ENG SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310685206.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2025-05-02
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

The existing polypropylene hollow fiber membranes have problems such as low gas separation efficiency and susceptibility to contamination and blockage in the wastewater deamination process. The thermal phase preparation process requires organic solvents and extraction processes, which consumes energy.

Method used

By preparing nanospherical barium sulfate inorganic particles and melt blending them with polypropylene resin and fluoropolymer, a single screw extrusion mechanism is used to prepare a polypropylene hollow fiber membrane. The inorganic particles are used as a gas transportation medium, and the fluoropolymer improves the pollution resistance of the membrane pores.

Benefits of technology

The gas separation efficiency is significantly improved, the pollution resistance of membrane pores is enhanced, the preparation cost is reduced, and the use of solvents and extractants is avoided, forming a mixed matrix polypropylene hollow fiber membrane with good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116550165B_ABST
    Figure CN116550165B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation. The preparation method first prepares nanometer barium sulfate inorganic particles as a gas transport medium, then melts and blends the inorganic particles, a fluorine-containing polymer and a polypropylene raw material to prepare a hollow fiber spinning masterbatch, uses a screw extruder in conjunction with a hollow spinneret to extrude and draw the spinning raw material, and prepares a mixed matrix polypropylene hollow fiber membrane containing an inorganic functional material and an organic fluorine-containing material. The mixed matrix polypropylene hollow fiber membrane is used for degassing or aeration in the field of water treatment. The mixed matrix polypropylene hollow fiber membrane prepared by the invention improves gas separation efficiency and membrane pore pollution resistance, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment filtration membranes, and in particular relates to a preparation method and application of a mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation. Background Art

[0002] Ammonia nitrogen is a common pollutant in industrial wastewater. It has a wide range of sources and is very harmful. The treatment and recovery of ammonia nitrogen in wastewater is of great significance to environmental protection. Reasonable recycling and utilization can also produce certain economic benefits. At present, the processes for treating ammonia nitrogen-containing wastewater at home and abroad are roughly divided into physical and chemical methods, biological methods, ion exchange methods, membrane separation methods, etc. Among them, membrane separation technology is a method with relatively low energy consumption and does not produce new pollutants. It is suitable for solid-liquid separation, gas-liquid separation, and purification and concentration of materials. In the field of wastewater degassing, membrane separation materials that have been applied include polypropylene (PP), polyvinylidene fluoride (PVDF), polysulfone (PS), polytetrafluoroethylene (PTFE) and other materials. Among them, polypropylene material has been domestically produced. It is insoluble in organic solvents at room temperature, has good acid and alkali resistance and biological corrosion resistance. It is a very cost-effective membrane polymer. Its raw material price is much lower than PS, PVDF and PTFE. PP hollow fiber membrane is prepared by melt-stretching method. Unlike the membrane making process of PS, PVDF and PTFE materials, this membrane making process does not use organic solvents to cause pores, thus avoiding environmental pollution and solvent recovery costs caused by the membrane making process. At present, this membrane material still has some shortcomings. The PP hollow fiber membrane prepared by melt-stretching method has high requirements for wastewater quality, because the membrane pores are easily contaminated by particulate impurities, and when water enters the membrane pores, it is easy to cause the membrane pores to be blocked, resulting in reduced gas separation efficiency.

[0003] The preparation process of PP hollow fiber membrane by thermophase method requires organic solvent and extraction process, which consumes energy.

[0004] China's invention patent CN201310473160.3 discloses "a method for anti-pollution modification of polypropylene hollow fiber membrane components", which selects a compound with strong hydrophilicity and containing more active groups as a modifier, adsorbs it on the surface of the porous membrane component, and then coordinates and complexes with an inorganic antibacterial agent to immobilize it on the polypropylene hollow fiber membrane component, thereby preparing a polypropylene hollow fiber membrane component with hydrophilic antibacterial properties. This invention performs hydrophilic antibacterial modification on PP hollow fiber membranes, which is different from the preparation principle, technical route and use of this patent.

[0005] China's invention patent CN201310485951.8 discloses "an inorganic nanoparticle-enhanced polypropylene hollow fiber microporous membrane and its preparation method". This method adopts the method of melt blending inorganic nanoparticles treated with coupling agents and diluents in polypropylene resin, and adopts the thermal induced phase separation method to prepare inorganic nanoparticle-enhanced polypropylene hollow fiber separation membrane, which has excellent mechanical strength, uniform pore size distribution and good hydrophilicity. The invention adopts the thermal induced phase separation method to prepare the membrane, and the addition of inorganic particles (CaCO3, SiO2, TiO2) has a mechanical enhancement effect, while the nano inorganic particles BaSO4 used in the present invention have a medium effect of increasing the gas transport speed, which is different from the preparation principle and technical route of the present invention. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] As one aspect of the present invention, the present invention provides a method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination, which comprises:

[0008] (1) Preparation of inorganic barium sulfate particles as a gas transport medium: anhydrous barium chloride is placed in an alcohol solution; ammonium sulfate is placed in an alcohol-water mixed solution and aminotrimethylenephosphonic acid is added; the two solutions are heated and stirred separately, and then the two solutions are quickly mixed, reacted, centrifuged, washed, and dried to obtain nano-spherical inorganic barium sulfate particles;

[0009] (2) melt-blending polypropylene resin, barium sulfate inorganic particles, and fluorine-containing polymer to prepare polypropylene spinning masterbatch, adding the masterbatch to a single-screw extruder, introducing an inert gas into the spinneret cavity during the extrusion process, and solidifying the spinning melt in the air after being extruded through the hollow spinneret, and obtaining polypropylene primary hollow fibers by drawing and winding, wherein the drawing ratio is 1500 to 2500, thereby obtaining polypropylene primary hollow fibers;

[0010] (3) The polypropylene primary hollow fiber is heat treated at a temperature of 130-140° C. for 1 hour, and after cooling, a polypropylene hollow fiber with hard elasticity is obtained, and the polypropylene hollow fiber is stretched and heat-set to obtain a polypropylene hollow fiber membrane with a microporous structure.

[0011] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation according to the present invention: in step (3), the stretching is performed at a speed of 5 to 10 mm / min to 2.5 to 3.5 times the original length.

[0012] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation according to the present invention: in step (2), the inert gas is nitrogen.

[0013] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation according to the present invention: in step (2), the fluorine-containing polymer is a copolymer of perfluoroethyl acrylate and methacrylate, and its weight average molecular weight is 5000 to 12000.

[0014] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation according to the present invention: in step (2), the weight average molecular weight of the copolymer of perfluoroethyl acrylate and methacrylate is 8,000.

[0015] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation described in the present invention: in step (2), the mass percentage ratio of the polypropylene resin, the barium sulfate inorganic particles and the fluorine-containing polymer is 98-99.4wt%: 0.3-1wt%: 0.3-1wt%, and the sum of each component is 100%.

[0016] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deamination described in the present invention: in step (1), the mass ratio of the raw materials barium chloride, ammonium sulfate, alcohol solution, aminotrimethylenephosphonic acid and water is 5%:3%:68.5-75.5%:0.5%:16-23%, and the sum of each component is 100%.

[0017] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation according to the present invention: in step (1), the alcohol solution is one of ethylene glycol, propylene glycol and glycerol.

[0018] As a preferred embodiment of the method for preparing the mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation according to the present invention: in step (1), the reaction is carried out for a reaction time of 20 to 60 minutes.

[0019] The beneficial effects of the present invention are as follows: the polypropylene hollow fiber membrane prepared by the present invention has significantly lower cost than polyvinylidene fluoride and polytetrafluoroethylene membranes on the market, and does not use solvents and extractants; compared with similar polypropylene hollow fiber membranes prepared by the melt-stretching method, it has higher gas separation efficiency and better backwashing performance, and the membrane pore pollution resistance is greatly improved. The polypropylene hollow fiber membrane prepared by the present invention can be used in a variety of gas separation and water treatment aeration fields, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0021] Figure 1 This is a physical picture of the polypropylene hollow fiber membrane prepared in Example 5.

[0022] Figure 2 This is the SEM image of the polypropylene hollow fiber membrane prepared in Example 5. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0024] Embodiment 1:

[0025] A method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deammoniation comprises the following steps:

[0026] (1) Anhydrous barium chloride is placed in a certain amount of alcohol solution; ammonium sulfate is placed in a certain amount of alcohol-water mixed solution, and a certain amount of aminotrimethylenephosphonic acid is added; the two prepared solutions are placed in a 90°C water bath for heating and stirring for 10 minutes, and then the two solutions are quickly mixed, and the mass ratio of the raw materials barium chloride, ammonium sulfate, ethylene glycol, aminotrimethylenephosphonic acid and water is 5%:3%:75.5%:0.5%:16%. After reacting for 60 minutes, centrifuge and wash away the residual alcohol solution with anhydrous ethanol, and the product is dried at 75°C in an electric heating blast oven and sealed for storage to obtain nano-spherical barium sulfate inorganic particles.

[0027] (2) Polypropylene resin (model T30s), barium sulfate inorganic particles and fluorine-containing polymer (copolymer of perfluoroethyl acrylate and octadecyl methacrylate, Mw weight average molecular weight 8000) were mixed in a mass fraction of 99%:0.5%:0.5%, and melt blended by a twin-screw extruder, and the melt temperature was set to 250°C to prepare polypropylene spinning masterbatch. The plasticized mixture particles were added to a single-screw extruder, and the melt temperature and spinneret temperature were 210°C and 190°C respectively. Nitrogen was introduced into the spinneret cavity during the extrusion process. The spinning melt was solidified in the air after being extruded through the hollow spinneret. The inner and outer diameters of the spinneret were 15 mm and 20 mm. Polypropylene primary hollow fibers were obtained by drawing and winding, and the drawing ratio was 2500.

[0028] (3) The polypropylene nascent hollow fiber obtained above was placed in an electric hot air oven and heat treated at 135°C for 1 hour. After cooling, a polypropylene hollow fiber with hard elasticity was obtained. The fiber was fixed on the clamp of the stretching oven, the clamp length was adjusted, and the fiber was stretched to 3.5 times the original length at a speed of 7 mm / min. After the stretching was completed, the fiber was heat-set for 1 hour. After cooling, a polypropylene hollow fiber membrane with a microporous structure was obtained.

[0029] The experiment was repeated several times and the average value was taken. The test showed that the water contact angle of the hollow fiber microporous membrane prepared in this embodiment was 118.5°, the average pore size was 0.51 μm, the maximum pore size was 0.69 μm, and the initial gas flux was 50.2 L·m -2 ·s -1 (Test pressure 0.1MPa), the average ammonia removal rate of the membrane module after 2 hours of operation was 89.2% (operating parameters: membrane area 0.5m 2 , ammonia nitrogen treatment liquid concentration 3g / L, volume 1L, dilute sulfuric acid absorption liquid concentration 0.6mol / L, volume 1L, treatment liquid and absorption liquid flow rate 1L / min, operating temperature 40·).

[0030] Embodiment 2:

[0031] Compared with Example 1, the mass ratio of the raw materials barium chloride, ammonium sulfate, ethylene glycol solution, aminotrimethylenephosphonic acid and water in step (1) was changed to 5%:3%:71.5%:0.5%:20%, the reaction time was changed to 40 min, and the other conditions remained unchanged.

[0032] The experiment was repeated several times and the average value was taken. The test showed that the water contact angle of the hollow fiber microporous membrane prepared in this embodiment was 119.3°, the average pore size was 0.46 μm, the maximum pore size was 0.58 μm, and the initial gas flux was 43.7 L·m -2 .s -1 (Test pressure 0.1MPa), the ammonia removal rate of the membrane module after running for 2 hours was 92.3%.

[0033] Compared with Example 1, Example 2 increases the water content in the reaction system, reduces the content of the alcohol solution in the reaction system, and reduces the reaction time, so that the particle size of the prepared barium sulfate inorganic particles is reduced. The smaller particle size makes the stress distribution of the polypropylene fiber during spinning drawing and post-stretching more uniform, so the average pore size and the maximum pore size are reduced by 0.05μm and 0.11μm, respectively. On the other hand, the reduction in particle size increases the specific surface area of ​​the inorganic particles, thereby improving the ability to adsorb ammonia. Although the gas flux is reduced, the water blockage of the membrane pores during operation is also reduced accordingly. Therefore, the ammonia removal rate is increased by 3.5% compared with Example 1.

[0034] Embodiment 3:

[0035] Compared with Example 2, the mass ratio of the polypropylene resin, the barium sulfate inorganic particles and the fluorine-containing polymer in step (2) is changed to 98%:1%:1%.

[0036] The experiment was repeated several times and tested. After testing, the hollow fiber microporous membrane prepared in this embodiment had a water contact angle of 124.4°, an average pore size of 0.45 μm, a maximum pore size of 0.61 μm, and an initial gas flux of 43.5 L·m -2 ·s -1 (Test pressure 0.1 MPa), the ammonia removal rate of the membrane module after running for 2 hours was 95.1%.

[0037] Compared with Example 2, Example 3 increases the amount of barium sulfate inorganic particles and fluorine-containing polymer added to the polypropylene hollow fiber membrane. The test results show that due to the strong hydrophobicity of the fluorine-containing polymer, the water contact angle of the hollow fiber membrane increases by 4.3%, which is 10% higher than that of Control Example 1, making the membrane pores of the hollow fiber membrane less likely to be clogged during use. On the other hand, the increase in barium sulfate content also enhances the ammonia adsorption capacity of the membrane, thereby improving the ammonia removal rate.

[0038] Embodiment 4:

[0039] Compared with Example 3, the drafting ratio after step (3) is changed to 3 times, and other conditions remain unchanged.

[0040] The experiment was repeated several times and the average value was taken. The test showed that the water contact angle of the hollow fiber microporous membrane prepared in this embodiment was 124.6°, the average pore size was 0.35 μm, the maximum pore size was 0.52 μm, and the initial gas flux was 36.3 L·m -2 ·s -1 (Test pressure 0.1MPa), the ammonia removal rate of the membrane module after running for 2 hours was 98.7%.

[0041] In Example 4 compared with Example 3, the stretching ratio in step (3) is reduced from 3.5 times to 3 times, so that the average pore size and the maximum pore size of the hollow fiber membrane are reduced by 0.1 μm and 0.09 μm, respectively. Therefore, although the gas flux is significantly reduced, the reduction in pore size also reduces the number of membrane pores that are blocked during use, thereby improving the ammonia removal rate.

[0042] Embodiment 5:

[0043] Compared with Example 4, the spinning draft ratio was changed to 2000, and other conditions remained unchanged.

[0044] The experiment was repeated several times and the average value was taken. The test showed that the water contact angle of the hollow fiber microporous membrane prepared in this embodiment was 124.3°, the average pore size was 0.31 μm, the maximum pore size was 0.48 μm, and the initial gas flux was 32.8 L·m -2 ·s -1 (Test pressure 0.1MPa), the ammonia removal rate of the membrane module after running for 2 hours was 99.2%.

[0045] Compared with Example 4, Example 5 reduces the spinning draw ratio, and the average pore size and the maximum pore size are slightly reduced. At the same time, the reduction in the draw ratio causes a slight increase in the inner diameter of the hollow fiber membrane. Since polypropylene itself is hydrophobic, the reduction in the inner diameter increases the resistance to water flow inside the hollow fiber membrane, thereby increasing the ammonia removal rate to 99.2%.

[0046] Comparative Example 1

[0047] Compared with Example 5, no barium sulfate inorganic particles and fluorine-containing polymer are added, and the synthesis of barium sulfate and the masterbatch preparation process are not required. The other conditions and preparation methods are the same as those in Example 5.

[0048] (1) Polypropylene resin (model T30s) was added into a single screw extruder, and the melt temperature and spinneret temperature were 210°C and 190°C, respectively. During the extrusion process, nitrogen was introduced into the spinneret cavity. The spinning melt was solidified in the air after being extruded through the hollow spinneret. The inner and outer diameters of the spinneret were 15 mm and 20 mm. Polypropylene primary hollow fibers were obtained by drawing and winding, and the drawing ratio was 2000.

[0049] (2) The polypropylene nascent hollow fiber obtained above was placed in an electric heating blast oven and heat treated at 135°C for 1 hour. After cooling, a polypropylene hollow fiber with hard elasticity was obtained. The fiber was fixed on the clamp of the stretching oven, the clamp length was adjusted, and the fiber was stretched to 3 times the original length at a speed of 7 mm / min. After the stretching was completed, the fiber was heat-set for 1 hour. After cooling, a polypropylene hollow fiber membrane with a microporous structure was obtained.

[0050] The experiment was repeated several times and tested. After testing, the hollow fiber microporous membrane prepared in this embodiment had a water contact angle of 113.1°, an average pore size of 0.32 μm, a maximum pore size of 0.50 μm, and an initial gas flux of 33.1 L·m -2 ·s -1 (Test pressure 0.1MPa), the ammonia removal rate of the membrane module after running for 2 hours was 80.2%. Compared with Example 5, there was no significant difference in pore size and gas flux, but the water contact was 10% smaller, and the ammonia removal rate was 19% less at the same time, which shows that the modified polypropylene hollow fiber membrane with added gas transport medium barium sulfate and fluorine-containing polymer has a higher ammonia removal efficiency.

[0051] Comparative Example 2

[0052] Compared with Example 5, no fluorine-containing polymer is added, the polypropylene resin and the barium sulfate inorganic particles are mixed in a mass fraction ratio of 99%:1%, and the other process conditions and preparation methods are the same as those in Example 5.

[0053] The experiment was repeated several times and tested. After testing, the hollow fiber microporous membrane prepared in this embodiment had a water contact angle of 108.2°, an average pore size of 0.33 μm, a maximum pore size of 0.52 μm, and an initial gas flux of 35.6 L·m -2 ·s -1 (Test pressure 0.1MPa), the ammonia removal rate of the membrane module after running for 2 hours was 87.7%. Compared with the control example 1, the water contact angle of the hollow fiber membrane was reduced because the barium sulfate inorganic particles had a certain hydrophilicity, and the ammonia removal rate was increased because the barium sulfate inorganic particles played a certain role in promoting the adsorption and transfer of ammonia.

[0054] Comparative Example 3

[0055] Compared with Example 5, no barium sulfate inorganic particles are added, the polypropylene resin and the fluorine-containing polymer are mixed in a mass fraction ratio of 99%:1%, and the other process conditions and preparation method are the same as those in Example 5.

[0056] The experiment was repeated several times and tested. After testing, the hollow fiber microporous membrane prepared in this embodiment had a water contact angle of 122.2°, an average pore size of 0.31 μm, a maximum pore size of 0.48 μm, and an initial gas flux of 33.7 L·m -2 ·s -1 (Test pressure 0.1MPa), the ammonia removal rate of the membrane module after running for 2 hours was 85.6%. Compared with the control example 1, without adding inorganic barium sulfate particles, only adding fluorine-containing polymers increased the water contact angle of the hollow fiber membrane, improved the anti-pollution ability of the membrane, reduced the blockage of the membrane pores, and increased the ammonia removal rate.

[0057] Comparative Example 4

[0058] Compared with Example 5, the polypropylene resin, the barium sulfate inorganic particles and the fluorine-containing polymer are mixed in a mass fraction ratio of 96%:2%:2%, and the other process conditions and preparation methods are the same as those in Example 5.

[0059] The experiment was repeated several times and tested. After testing, the hollow fiber microporous membrane prepared in this embodiment had a water contact angle of 124.5°, an average pore size of 0.45 μm, a maximum pore size of 0.78 μm, and an initial gas flux of 54.4 L·m -2 ·s -1(test pressure 0.1MPa), the ammonia removal rate of the membrane assembly after running for 2 hours was 85.4%. Comparative Example 4 increased the addition amount of barium sulfate inorganic particles and fluoropolymers. The test results showed that the average pore size and maximum pore size of the membrane increased significantly, and the gas flux also increased significantly, but the ammonia removal efficiency decreased significantly, because the higher addition amount caused the hollow fiber to produce uneven stress during stretching, and the inorganic particles gathered in the fiber, followed by the appearance of larger stretching holes, which easily caused the blockage of the membrane pores and reduced the removal efficiency. Therefore, the increase in the addition amount of barium sulfate and fluoropolymers within a certain range is beneficial to the improvement of membrane performance, and exceeding a certain range will reduce the membrane performance.

[0060] Comparative Example 5

[0061] Compared with Example 5, PTFE (model Solvay F5A) is used to replace the fluorine-containing polymer of the present invention, and the other process conditions and preparation methods are the same as those of Example 5.

[0062] The experiment was repeated several times and tested. After testing, the hollow fiber microporous membrane prepared in this embodiment had a water contact angle of 116.7°, an average pore size of 0.38 μm, a maximum pore size of 0.54 μm, and an initial gas flux of 38.7 L·m -2 ·s -1 (test pressure 0.1MPa), the ammonia removal rate of the membrane assembly for 2 hours is 86.1%. Compared with Example 5, the fluoropolymer used in the present invention is replaced with a perfluoropolymer PTFE (polytetrafluoroethylene). From the test results, it can be seen that the effect of PTFE on improving the fiber water contact angle is relatively low, the membrane pore size is slightly increased, and the ammonia removal efficiency is 13.1% lower than that of Example 5. The reason for this phenomenon may be that the fluoropolymer used in the present invention is a fusible macromolecular hydrophobic material, and the PTFE perfluoropolymer cannot be melted during polymer processing, and the particle size is greater than 1μm, and it cannot be melted and evenly distributed with polypropylene. Therefore, the fiber is affected by uneven stress during stretching, which will produce uneven pore size and macropores, so the ammonia removal efficiency is low.

[0063] Table 1

[0064]

[0065] The present invention overcomes the problem that the membrane pores are easily contaminated by particulate impurities, and that water entering the membrane pores easily leads to clogging of the membrane pores, resulting in reduced gas separation efficiency, by controlling the crystallization process, adsorbing inorganic particles, and hydrophobic modification of fluoropolymers. The present invention evenly distributes functional inorganic particles and fluoropolymers in the fibers, and the inorganic particles participate in the gas separation process as transport media. The fluoropolymers improve the pollution resistance of the membrane pores, forming a mixed matrix polypropylene hollow fiber membrane that will not fail due to long-term use and backwashing.

[0066] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination, characterized in that: include, (1) Preparation of inorganic barium sulfate particles as a gas transport medium: anhydrous barium chloride is placed in an alcohol solution; ammonium sulfate is placed in an alcohol-water mixed solution and aminotrimethylenephosphonic acid is added; the two solutions are heated and stirred separately, and then the two solutions are quickly mixed, reacted, centrifuged, washed, and dried to obtain nano-spherical inorganic barium sulfate particles; (2) melt-blending polypropylene resin, barium sulfate inorganic particles and fluorine-containing polymer to prepare polypropylene spinning masterbatch, adding the masterbatch to a single-screw extruder, introducing an inert gas into the spinneret cavity during the extrusion process, and solidifying the spinning melt in the air after being extruded through the hollow spinneret. The polypropylene primary hollow fiber is obtained by drawing and winding, and the drawing ratio is 1500-2500; (3) heat treating the polypropylene primary hollow fiber at a temperature of 130-140° C. for 1 hour, cooling to obtain a polypropylene hollow fiber having hard elasticity, stretching and heat setting to obtain a polypropylene hollow fiber membrane having a microporous structure; In step (2), the fluorine-containing polymer is a copolymer of perfluoroethyl acrylate and methacrylate, and its weight average molecular weight is 5000-12000.

2. The method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination according to claim 1, characterized in that: In step (3), the stretching is performed at a speed of 5 to 10 mm / min to 2.5 to 3.5 times the original length.

3. The method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination according to claim 1 or 2, characterized in that: In step (2), the inert gas is nitrogen.

4. The method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination according to claim 1, characterized in that: In step (2), the weight average molecular weight of the copolymer of perfluoroethyl acrylate and methacrylate is 8000.

5. The method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination according to claim 1 or 2, characterized in that: In step (2), the mass percentage ratio of the polypropylene resin, the barium sulfate inorganic particles and the fluorine-containing polymer is 98-99.4 wt%: 0.3-1 wt%: 0.3-1 wt%, and the sum of the components is 100%.

6. The method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination according to claim 1 or 2, characterized in that: In step (1), the alcohol solution is one of ethylene glycol, propylene glycol and glycerol.

7. The method for preparing a mixed matrix polypropylene hollow fiber membrane for wastewater deamination according to claim 1 or 2, characterized in that: In step (1), the reaction is carried out for a time of 20 to 60 minutes.

8. Use of the polypropylene hollow fiber membrane prepared by the preparation method according to claim 1 in deammoniation of wastewater.

Citation Information

Patent Citations

  • Inorganic nanoparticle-reinforced polypropylene hollow fiber microporous membrane and its preparation method

    CN104548950B

  • Anti-pollution modification method of polypropylene hollow fiber membrane module

    CN104548959A

  • Method for preparing lasting super-hydrophobic modified polypropylene hollow fiber membrane

    CN102688704A

  • Porous polymer membrane

    CN103975005A